The Concept of Multicultural Education in Efforts to Prevent Religious Conflict in Indonesia - Amirudin, Ja’far; Ruswandi, Uus; Arifin, Bambang Samsul (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to analyze the concept of multicultural education in efforts to prevent religious conflicts in Indonesia. The approach taken is library research, where the study is conducted by collecting data or scientific writings that are literary in nature. The data collection method in this research is derived from the sources used, meaning that the data sources are the subjects from which the information is obtained. The results of the discussion mentioned that efforts to prevent religious conflict in Indonesia, first, to unite differences and attitudes. Second, building the structure of religious understanding. Third, religious development policy resolution. Fourth, resolution of social conflict / violence expectation expectations. With this concept, it is expected to increase their awareness so that they always behave humanist, pluralist, and democratic.